A randomized double blind study of the effect of finasteride on hair growth in male patients of androgenetic alopecia - Prasad H; Khanna Neena; Pandhi R (Wolters Kluwer Medknow Publications, 2005)
Eighty male patients with AGA, not treated in the previous 6 months were enrolled in this randomized, double blind, placebo controlled trial to assess the safety and efficacy of finasteride, 1mg daily, on hair growth. Patients were randomized into 2 groups: Group 1 received 1 mg of finasteride daily and Group 2 received a placebo for a period of 12 months. Efficacy was assessed by hair counts, photographic records, patient′s self-assessment questionnaire and clinical assessment. Safety was assessed by history taking and laboratory parameters. A total of 39 patients completed the study. Finasteride was rated superior to placebo with respect to all efficacy measures. At the end of study, finasteride treated patients had a mean increase of 20.56±4.73 hairs compared to a decrease of 9.56±5.53 hairs in placebo treated patients. Photographically, 69.56% of finasteride treated patients were rated as improved at 12 months compared to only 6.25% of placebo treated patients. Ten (25%) of finasteride treated patients developed adverse effects (5-decreased libido as well as erectile dysfunction, 4-erectile dysfunction, 1-decreased libido). Finasteride in comparison to placebo was effective in promoting hair growth in male patients of AGA. However, the side effects to the drug were high in this study.